2003
DOI: 10.1897/02-499
|View full text |Cite
|
Sign up to set email alerts
|

Development and field validation of a predictive copper toxicity model for the green alga Pseudokirchneriella subcapitata

Abstract: In this study, the combined effects of pH, water hardness, and dissolved organic carbon (DOC) concentration and type on the chronic (72-h) effect of copper on growth inhibition of the green alga Pseudokirchneriella subcapitata were investigated. Natural dissolved organic matter (DOM) was collected at three sites in Belgium and The Netherlands using reverse osmosis. A full central composite test design was used for one DOM and a subset of the full design for the two other DOMs. For a total number of 35 toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
119
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 48 publications
13
119
2
Order By: Relevance
“…The DOC effects evaluated in the present study were based on laboratory exposures to Suwannee River NOM, which is a commonly used natural form of DOC for metal toxicity studies. Although it is recognized that natural forms of DOC can vary in composition and, hence, their metal binding properties [35], the effects of DOC complexation even in the face of this variability is well characterized using bioavailability-based models [15,16]. Although water quality effects on algal toxicity were broadly similar, hardness relationships differed markedly with pH.…”
Section: Discussionmentioning
confidence: 99%
“…The DOC effects evaluated in the present study were based on laboratory exposures to Suwannee River NOM, which is a commonly used natural form of DOC for metal toxicity studies. Although it is recognized that natural forms of DOC can vary in composition and, hence, their metal binding properties [35], the effects of DOC complexation even in the face of this variability is well characterized using bioavailability-based models [15,16]. Although water quality effects on algal toxicity were broadly similar, hardness relationships differed markedly with pH.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include 71 the acidification of soils [7][8][9][10][11][12][13][14] and surface waters [15] , trace metal behaviour in soils [16][17][18][19][20][21][22] , surface 72 waters [23][24][25][26][27][28][29][30][31] and groundwaters [32] , lake sediment diagenesis [33,34] , rare earth geochemistry [35-73 37] , iron and manganese geochemistry [38][39][40][41] , radionclide geochemistry [42][43][44][45] , organic matter 74 solubility in soils [46,47] , catchment modelling [48,49] , interactions of metals with biota [50,51] , 75 ecotoxicology [52][53][54][55][56][57][58][59] and Critical Loads …”
Section: Tipping Et Al Humic Ion-binding Model Vii_revisionmentioning
confidence: 99%
“…Similar results were observed for us in leaves of P. stratiotes to both enzymes. Srivastava et al (2006) suggested that, high increase in activities of these enzymes could mean a breakdown of SCHAMPHELAERE et al 2003). Statistical advancement in ecotoxicology is necessary to improve the guidelines in this area.…”
Section: Apx Activity In Rootsmentioning
confidence: 99%
“…The disadvantage of this type of design is twofold: the effect of only one parameter is studied, and possible interactions of different parameters cannot be assessed . In contrast, the advantage of the Central Composite Design (CCD) is that it can generate a maximum amount of information on the direct effect of test variables and their interactions while testing a minimum number of combinations (DE SCHAMPHELAERE et al, 2003).Thus, a way to develop, improve and optimize processes consists of applying the CCD and the Response Surface Methodology (RSM), which can be very useful and advantageous for both the evaluation and optimization of some capacidade parameters. More specifically, the experimental design helps the researcher to verify if changes in the independent variables produce a statistically significant variation of the observed response, and this approach can be used each time this type of information is required (FURLANETTO et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation